Maṣlaḥa and the purpose of the law : Islamic discourse on legal change from the 4th/10th to 8th/14th century - Opwis, Felicitas Meta Maria. (Studies in Islamic Law and Society, 2010)
Focusing on writings of legal theory by leading jurisprudents from al-Jaṣṣāṣ (d. 370/980) to al-Shāṭibī (d. 790/1388), this study traces the Islamic discourse on legal change. It looks at the concept of maṣlaḥa (people's well-being) as a method of extending and adapting God's law, showing how it evolves from an obscure legal principle to being interpreted as the all-encompassing purpose of God's law. Discussions on maṣlaḥa's epistemology, its role in the law-finding process, the limits of human investigation into divinecommands, and the delineation of the sphere of religious law in Muslim society highlight the interplay between law, theology, logic, and politics that make maṣlaḥa a viable vehicle of legal change up to the present.